SISTEM PEMBAGIAN WARISAN MASYARAKAT WONOANTI: PERSPEKTIF HUKUM ISLAM DAN ADAT - Adiriki, Danu; Wibowo, Muhammad Kurniawan Budi; Muslimin, Edy (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to describe the inheritance distribution practices in the community of Wonoanti Village, Tulakan District, Pacitan Regency, and to analyze them from the perspective of Islamic law. A descriptive qualitative approach was employed, using data collection techniques such as in-depth interviews and field observations. The findings reveal that the inheritance distribution process is primarily carried out through family deliberation, prioritizing local customary values over formal Islamic legal provisions. The community tends to emphasize justice and family harmony in determining inheritance shares, despite having an awareness of the importance of Islamic law as a normative guideline. These findings indicate an interaction between local customs and religious teachings in inheritance practices, reflecting the flexibility of Islamic law within specific socio-cultural contexts.